2014
DOI: 10.1038/ki.2013.301
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and the risk of all-cause and cardiac mortality in hemodialysis patients: agent provocateur or innocent bystander?

Abstract: There have been previous reports of hypomagnesemia associated with increased cardiovascular risk in hemodialysis patients. However, these reports were often confounded by hypomagnesemia linked to increased patient co-morbidity. Sakaguchi and colleagues now report increased patient survival, with both reduced all-cause and cardiovascular mortality for those with mild hypomagnesemia, compared to patients with both normal and low serum magnesium concentrations, and also those with moderate hypomagnesemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…In our study, MHD patients with Mg < 2.4 mg/dl had worse nutritional status, which comprised lower values of serum albumin, nPNA, GNRI, phosphate, and uric acid, compared with patients with Mg ≥ 2.4 mg/dl. Taken together with the results of the previous reports [ 9 , 16 , 20 22 ], our findings indicate that nutritional factors greatly influence hypomagnesemia, and that such factors might partly contribute to the poor outcomes described by Courivaud et al [ 11 ]. Thus, hypomagnesemia appears to be correlated with mortality; whether Mg plays a causal role in this relationship remains unclear [ 4 , 11 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, MHD patients with Mg < 2.4 mg/dl had worse nutritional status, which comprised lower values of serum albumin, nPNA, GNRI, phosphate, and uric acid, compared with patients with Mg ≥ 2.4 mg/dl. Taken together with the results of the previous reports [ 9 , 16 , 20 22 ], our findings indicate that nutritional factors greatly influence hypomagnesemia, and that such factors might partly contribute to the poor outcomes described by Courivaud et al [ 11 ]. Thus, hypomagnesemia appears to be correlated with mortality; whether Mg plays a causal role in this relationship remains unclear [ 4 , 11 ].…”
Section: Discussionsupporting
confidence: 88%
“…Clinical studies have produced inconsistent results regarding the association between Mg levels and mortality, partly because hypomagnesemia is linked to an increased frequency of co-morbidities. It is unclear whether hypomagnesemia causes increased mortality as an independent risk factor or as an “innocent bystander” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…When examined as a continuous variable, we found that there was a trend towards higher death risk with Mg levels > 3 mg/dl, although not statistically significant. Prior data suggest that hypermagnesemia may inhibit PTH secretion, leading to low bone turnover and vascular calcification 51,52 as potential risk factors for CVD and death. However, our study did not show a significant correlation between baseline serum Mg and iPTH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, population-based studies of patients with chronic renal disease and congestive heart failure found that both lowest and highest magnesium ranges were independently associated with greater mortality, after adjusting for other comorbidities. 7,8 Although the effects of serum magnesium on clinical outcomes remain controversial, surveillance of serum magnesium levels is a common practice considering that it is a modifiable factor. 2,[9][10][11] Consensus among various experts recommends maintaining serum magnesium levels >2 mg/dL among patients at risk for arrhythmias.…”
mentioning
confidence: 99%